Integrated Silicon Photonic Crystals Toward Terahertz Communications. Issue 16 (25th June 2018) - Withayachumnankul, Withawat; Fujita, Masayuki; Nagatsuma, Tadao
Abstract: The terahertz frequency range locates between 0.1 and 10 THz. This range accommodates atmospheric windows with staggering absolute bandwidth. It holds a potential for point‐to‐point wireless communications with an aggregate capacity reaching terabit per second in a range up to a kilometer. This unique capability is envisaged for backhauls between base stations and for local area networks. To this end, efficiency and compactness of the transceivers are crucial for successful large‐scale adoption. However, state‐of‐the‐art terahertz front ends are based on radio‐frequency or photomixing technologies that are inefficient, bulky, or complicated. In principle, as a neighbor of the microwave and optics domains, the terahertz band can leverage technologies from both sides to overcome those challenges. Recently, low‐loss integrated circuits based on photonic crystal waveguides are developed for routing terahertz waves. Here, a progress report on core components, including waveguides and diplexers, is presented. Additionally, the interfacing of the platform with electronic sources and detectors on one end, and with antennas for free‐space coupling on the other end, is discussed. Currently, the platform can support terahertz communications at a data rate over 10 Gbit s −1 . Challenges and opportunities are discussed in the light of future development in this area. Abstract : This progress report gives an overview on photonic crystal waveguides aimed toward an integrated terahertz communications platform. The platform is expected to be broadband and highly efficient so to accommodate future terabits data links. The work draws principles from both the photonics and microwave domains to solve challenges specific to this frequency range.